Another Other Side of the Coin: Exchange Rate Movements and the Manufacturing Sector in Nigeria. (June 2018) - Orji, Anthony; Ogbuabor, Jonathan E.; Okeke, Chiamaka; Anthony-Orji, Onyinye I.
This study estimated the impact of exchange rate (EXCH) movements on the manufacturing sector in Nigeria over the period 1981–2016. Time series data and ordinary least square (OLS) estimation technique were employed in this study to address the specified objective. The variables analysed were EXCH, manufacturing GDP (MGDP), government capital expenditure, foreign direct investment (FDI), credit to private sector and value of imports. From the result, it is apparent that EXCH movements play a significant role in the manufacturing sector's performance in Nigeria. Specifically, the findings showed that EXCH, government capital expenditure (GCEXP), imports and FDI were positively related to MGDP, while credit to private sector was negatively related. Among others, the study recommends that the apex bank keep a closer watch on EXCH developments in order to keep formulating up-to-date policies that will ultimately enhance EXCH stability. This will largely contribute to the development of the manufacturing sector in the short and long run. JEL Classification: D51, F31, Q24